The role of classification in talent identification and development in Para sports - Fortin-Guichard, D.; Blaauw, E.; Van der Rijst, R.; Tweedy, S.; Mann, D.; Woods, M. (Talent development in Paralympic sport: Researcher and practitioner perspectives, 2022)
Talent identification in Para sports is aimless without classification. Classification is the process by which it is determined whether a Para athlete's impairment is sufficient for them to qualify to compete in Para sports, and if so, in which `class' they should compete. And because performance should be more severely impacted with each successive class, an individual's potential in Para sports should be considered relative to the class in which they will compete. Therefore, knowledge of a potential athlete's class is a vital step in determining the athlete's true potential in the sport. Moreover, sport federations sometimes seek to identify athletes from specific sport classes, for instance when seeking a balance of different levels of impairment within a team sport (e.g., Wheelchair Rugby). Robust classification systems that minimise the impact of impairment on performance outcomes within classes are vital to minimise the incentive for sports to more simply identify athletes with the least impairment within their class.